Spermidine and other functional phytochemicals in soybean seeds: Spatial distribution as visualized by mass spectrometry imaging. Issue 1 (19th December 2019) - Sagara, Tatsuya; Bhandari, Dhaka Ram; Spengler, Bernhard; Vollmann, Johann
Abstract: Soybean seeds contain phytochemicals such as polyamines and isoflavones, which have been identified as functional components mediating health benefits in association with the consumption of soy foods. While a clear picture of the spatial distribution of these components within the seed is lacking, such information would be important to enhance or reduce their concentration in respective foods through processing. Thus, the objective of the present study was to visualize the most relevant components with respect to their distribution in soybean seeds. Mature soybean seeds were subject to atmospheric‐pressure scanning‐microprobe matrix‐assisted laser desorption/ionization (AP‐SMALDI) combined with a Fourier‐transform orbital trapping mass spectrometer to generate high‐resolution chemical images of phytochemical distribution. Based on seed cross sections, differential distributions of functional components were found between soybean cotyledon and germ (shoot, hypocotyl, root) regions. Spermidine and spermine were present in higher concentrations in the germ rather than in cotyledons with highest concentrations in root and shoot meristem tissues. Differential concentrations of spermidine and other components between the germ and cotyledon regions were confirmed by seed fractioning. In contrast to polyamines spermidine and spermine, the different types of daidzein, glycitein, and genistein isoflavones were all visualized in root parenchyma tissue exclusively. Overall, mass spectrometry imaging of soybean seeds revealed clear insights into the differential distribution of functional phytochemicals. Based on their distribution and depending on specific needs, spermidine and isoflavones can either be enriched or reduced during food processing by separating cotyledon and germ fractions. Abstract : Spermidine is mediating various health effects through the induction of intracellular autophagy. In soybean, spermidine concentration is highest in the germ region of the embryo (shoot and root meristem tissues) as revealed by mass spectrometry imaging. Thus, separation of soybean germs during processing and food production can generate raw materials for the development of food supplements enriched in spermidine.